THE INFLUENCE OF ECOLOGICAL FACTORS ON TYPICAL RESPONSE OF LILIES - Antonets, M. O.; Antonets, O. A.; Milenko, О. H.; Sukhoviienko, A. A.; Vorvykhvist, M. S. (Scientific Progress & Innovations, 2021)
Lilies have a huge aesthetic impact on a person due to the unique variety of colors and beautiful decorative appearance. They are widely used for cultivation in parks and gardens, both planted separately and in groups near trees, shrubs, lawns, as well as for cutting and forcing. When it comes to color, shape, aroma, or flowering time, lilies are unmatched among bulbous plants. Therefore, the relevance of the topic is to identify the basic requirements for different types of lilies in Poltava region in terms of resistance to adverse environmental factors, taking into account the ability to maintain a high decorative effect. The aim of the study was to determine the influence of environmental factors on the typical response of lilies. To achieve this goal it was imperative to solve the following tasks: 1) Study the influence of sunlight on the typi-cal response of lilies; 2) Determine the effect of low temperatures in winter for the revival of lily vegetation; 3) Show the relationship to moisture of different hybrids of lilies; 4) Identify the decorative quality. The study was conducted in Hlobyne district of Poltava region in Lypove village on the territory of a private farm S=0.1 ha during 2018–2020. In total, 55 varieties of lilies are grown on the site. For the experiment, 17 varieties were taken, which were classified into six groups by nomenclature. They are Oriental hybrids, Asian hybrids, Longiflorum-Asian-Hybrids, Tubular / Orleans hybrids, Oriental-Tubular Hybrids, Longiflorum-Oriental hybrids. The subject of the research is varietal reaction of lilies. Taking into account the influence of such environmental factors as light, low temperatures and moisture on the typical response of lilies on the average during 2018–2020, the best hybrids for cultivation in Poltava region were identified. According to the obtained results for the formation of flower beds, it is recommended to use the following groups of lilies: Asian hybrids Lollypop, Tropical Breeze and Dimension and Oriental-Tubular hybrids Robert Swanson, Altari, Beverly Drems, Pearl Jennifer and African Lady. They are well adapted to environmental conditions and have high decorative qualities in plant height and inflorescences.